Impact of industrial effluents on water quality at the Tiram River, Kuantan Malaysia - Nor Hidayah, Muhamad Asri (2015)
Indera Mahkota 3 (IM3) is one of the industrial area at Kuantan, Pahang, Malaysia. The Tiram River is located near IM3 and being affected by the industrial activities. This study was carried out to identify the water quality of The Tiram River and to classify the river based on Water Quality Index (WQI) and National Water Quality Standards (NWQS), Malaysia. Water sample was collected from three different sampling locations from February to March. Eleven parameters were experimented such as pH, temperature, dissolved oxygen (DO), electrical conductivity (EC), turbidity, biological oxygen demand (BOD), chemical oxygen demand (COD), total suspended solids (TSS), ammoniacal nitrogen (AN), sulphate and phosphate. Based on the result, some parameters that received high impacts from industrial activities were DO, BOD, COD, AN and phosphate. Based on WQI, all sampling stations were classified as Class III. The lowest WQI value was 57.11 and the highest value was 62.91. Based on WQI and NWQS, the study river was slightly polluted and urgent treatment is required to control water pollution.